2011
DOI: 10.1111/j.1432-2277.2011.01219.x
|View full text |Cite
|
Sign up to set email alerts
|

High brain-natriuretic peptide level predicts cirrhotic cardiomyopathy in liver transplant patients

Abstract: Summary Cirrhotic cardiomyopathy may appear following liver transplantation. Brain‐natriuretic peptide (BNP) values exceeding 391 pg/ml or 567 pg/ml may partially reflect ventricular stress because of cardiac dysfunction or indicate cirrhotic cardiomyopathy, respectively. The aim of the study was to assess cardiac dysfunction in liver transplant patients and its correlation with BNP as a biomarker. From 1/2008 to 7/2009, 157 adult liver transplant recipients with proven cirrhosis were recruited for the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 33 publications
3
53
1
4
Order By: Relevance
“…We found that BNP was an independent predictor in multivariate Cox regression analysis, similar to previous results (Pimenta et al, 2010). BNP concentrations in patients with cirrhosis have been reported to be an independent predictor of medium-term (6-month) survival in hospitalized patients with decompensated cirrhosis, suggesting its utility in risk stratification of patients with advanced cirrhosis (Pimenta et al, 2010); this finder also was supported by the results of Saner et al (2011). This finding was not unexpected because, as mentioned above, increased BNP concentrations were found to be associated with the decompensation components of cirrhosis such as hepatic encephalopathy, esophageal varices, and ascites.…”
Section: Discussionsupporting
confidence: 90%
“…We found that BNP was an independent predictor in multivariate Cox regression analysis, similar to previous results (Pimenta et al, 2010). BNP concentrations in patients with cirrhosis have been reported to be an independent predictor of medium-term (6-month) survival in hospitalized patients with decompensated cirrhosis, suggesting its utility in risk stratification of patients with advanced cirrhosis (Pimenta et al, 2010); this finder also was supported by the results of Saner et al (2011). This finding was not unexpected because, as mentioned above, increased BNP concentrations were found to be associated with the decompensation components of cirrhosis such as hepatic encephalopathy, esophageal varices, and ascites.…”
Section: Discussionsupporting
confidence: 90%
“…B-type natriuretic peptide (BNP) is similarly cleaved from its pro-peptide and released from ventricular myocytes in response to ventricular wall stretch or myocardial ischaemia [56] , with the primary purpose of reducing cardiac hypertrophy and fibrosis [57] . Increased concentrations have been detected in cirrhosis, with levels correlating with the severity of liver disease, presence of diastolic dysfunction, myocardial hypertrophy and survival [46,49,58,59] . Preoperative levels of BNPs (BNP and NT-proBNP) are powerful independent predictors of cardiovascular events and mortality in patients undergoing non-cardiac surgery [60,61] , with further enhancement of this risk stratification seen with the additional measurement of postoperative levels [62,63] .…”
Section: Biomarkersmentioning
confidence: 99%
“…Cirrhotic cardiomyopathy results from multifactorial organic myocardial changes and is defined as systolic and diastolic cardiac dysfunction with co-existing electrocardiographic (ECG) abnormalities or abnormal serologic markers (brain natriuretic peptide [BNP], troponin 1, adrenomedullin) in patients with cirrhosis in the absence of cardiac diseases [1,2,4]. Patients with decompensated cirrhosis have been demonstrated to have elevated levels of the N-terminal prohormone of brain natriuretic peptide (NT-proBNP) and left ventricle (LV) diastolic dysfunction [5]. Cirrhotic cardiomyopathy is characterized by blunted contractile responsiveness to stress and/or altered diastolic relaxation with electrophysiological abnormalities in the absence of any other known cardiac disease, in patients with liver cirrhosis [6].…”
mentioning
confidence: 99%